Role of the geologic-geomorphic setting of the Río de la Plata estuary coastal landscape in controlling freshwater lenses shape and distribution. (June 2022) - Carol, E.; Cellone, F.; Tanjal, C.; Galliari, M.J.
Abstract: Sea level fluctuations during the Holocene led to the deposition of different sedimentary facies in the Argentinean littoral of the Río de la Plata estuary and the adjacent sea area. This work aims to analyze the role of the geologic – geomorphic setting related to the Holocene evolution of the coastal landscape of the Río de la Plata estuary in terms of its control over the shape and distribution of freshwater lenses for water supply. For this purpose, satellite image analysis, field surveys, Vertical Electrical Soundings (VES), and sediment tests from boreholes were carried out. In addition, water samples were taken for electrical conductivity (EC) measurement, and major ions and stable isotopes of the water molecule determination. The results show that the geological and geomorphological evolution of the Río de la Plata estuary gave rise to positive landforms composed of highly permeable sediments that favor rainwater infiltration, which is stored in the shape of lenses. EC measurements in groundwater below these landforms recorded low values indicative of freshwater with isotopic content similar to that of local – global rainfall. Furthermore, the VES study allowed the definition of the freshwater – saline water interface. The outcomes of this study show that a detailed and exhaustive analysis of the geological – geomorphic setting resulting from the Holocene evolution of coastal zones constitutes, along with hydrochemistry and geophysics, appropriate tools for the exploration of freshwater lenses in coastal areas. Highlights: Holocene landscape control over the shape and distribution of freshwater lenses. Freshwater lenses assessment by hydrochemistry and geophysics studies. Water supply in coastal areas conditioned by the geologic – geomorphic setting.